The Asian summer monsoon : characteristics, variability, teleconnections and projection - Liu, Yunyun; Liang, Ping; Sun, Ying (Elsevier, 2019)
The Asian Summer Monsoon: Characteristics, Variability, Teleconnections and Projection focuses on the connections between the Indian Summer and East Asian Summer Monsoons, also including the South China Sea Summer Monsoon. While these systems have profound differences, their interactions have significant impacts on the climatic regimes in the region and throughout the world. In summer, the ASM engine pumps moisture transported across thousands of miles from the Indian and Pacific Oceans to the monsoon regions, producing heavy rains over south and east Asia and its adjacent marginal seas. This book reviews the different subsystems and their impact, providing guidance to enhance prediction models. Synthesizes the connections between the East Asian Summer Monsoon, the Indian Summer Monsoon and the Asian Summer Monsoon systemIncludes subsections on holistic characteristics, sub-seasonal and interannual variability, teleconnection patterns, and projections of future changeConnects current theory and practice on Asian Monsoon forecasting, providing researchers with new skills and information to use in climate and weather forecasting